Pembelajaran Sejarah Berbasis Inklusi di SMA Negeri 9 Surakarta - Aisna Chantika Aslinda; Musa Pelu (Simpati, 2026)
This study examines inclusive history learning at SMA Negeri 9 Surakarta, focusing on planning, implementation, and the barriers and solutions in implementing inclusive education. The objective was to determine how history learning is implemented to support educational services for students with special needs (ABK). The study employed a qualitative approach with a case study method, with data collection techniques including interviews, observation, and documentation, analyzed descriptively. The results indicate that inclusive education planning is implemented through the equal implementation of the Merdeka Curriculum (Independent Curriculum) without a specific curriculum for ABK, with technical learning adjustments that take into account the characteristics of ABK as athletes with disabilities under the Ministry of Youth and Sports. History learning utilizes the same learning modules, along with adjustments to methods, flexibility in time, and the use of Google Classroom. Obstacles that emerged included limited learning time, limited infrastructure, the lack of Special Assistance Teachers (GPK), and uneven distribution of inclusive training. Solutions implemented included flexible learning, group work, technology utilization, teacher competency development, and collaboration with the NPCI (National Institute of Indonesia). Overall, inclusive education at SMA Negeri 9 Surakarta operates adaptively to meet the needs of students.